Images of Makkah and the Hajj in South Thailand: An Ethnographic and Theological Exploration - Christopher Mark Joll; Srawut Aree (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
This article explores the historical and contemporary importance of Makkah and the hajj for Malays in South Thailand. Our multi-disciplinary approach examines relevant historiographies, the insights of Islamic Studies scholars, and ethnographic data collected in Pattani’s provincial capital. We point out that in the outputs produced by literary networks located in Sumatra and the portion of Thai/Malay Peninsula once referred to as the Malay Sultanate of Pattani, references to Makkah were early to appear. Malays from Pattani may have primarily travelled to Makkah to perform the hajj, but following Pattani’s subjugation by Bangkok in the late 18th century, Makkah functioned as a refuge. Following a description of the prerequisites, preparations, and performances of the hajj in present-day Pattani, we identify and discuss motivations of fulfilment, forgiveness, and merit-making. We argue through our exploration of these historical, ethnographic, and theological factors that Makkah is much more than a site of pilgrimage, and that the performance of hajj is multi-faceted.